Pengaruh Penggunaan Tanaman Refugia terhadap Kelimpahan dan Biodiversitas Musuh Alami pada Tanaman Cabai Rawit (Capsicum Frutescens L.) - Riska Piola; Angry P Solihin; Fitriah S. Jamin (Transbahasa, 2025)
This study aims to determine the influence of refugia plants on the population, abundance, and biodiversity of natural enemies. The research was conducted from February to June 2024 in North Toto Village, Tilongkabila District, Bone Bolango Regency, Gorontalo Province. A randomized block design (RAK) was used with three treatments: control (P0), refugia (P1), and chemical insecticide (P2), each repeated four times. Data were analyzed using Analysis of Variance (ANOVA) and followed by Duncan's Multiple Range Test at a 0.05 significance level. Results showed that predator natural enemies consisted of 7 families in the control (P0), 9 families in the refugia treatment (P1), and 5 families in the insecticide treatment (P2). The dominant families were Coccinellidae (48.65%) in P0, Libellulidae (28.57%) in P1, and Sphecidae (44.44%) in P2. The population of natural enemies in refugia was higher at 21 and 35 HST. The diversity index in all treatments was categorized as moderate. For pollinators, P0 had 3 families, P1 had 7, and P2 had only 3, with Apidae dominating all treatments, particularly in P1 (27 individuals). The population of pollinators in refugia reached 3.50 individuals at 63 HST, higher than in other treatments. Refugia treatment was dominated by Apidae (35.06%), Nymphalidae (18.18%), and Andrenidae (15.58%). The findings highlight the positive role of refugia in supporting natural enemy populations and the negative impact of insecticides on biodiversity.